Efektivitas Model Pembelajaran Inkuiri Terbimbing Berbantuan Bahan Ajar SIGAR Terhadap Hasil Belajar IPAS Kelas VI SD 2 Bulung Kulon - Rohmah Nur Anisa; Yuni Ratnasari; Sekar Dwi Ardianti (Jurnal Kajian Pendidikan IPA, 2026)
This study aims to evaluate the extent to which student learning outcomes in IPAS subjects improve when using a guided inquiry learning model assisted by SIGAR (Simulation of Earth's Rotation and Revolution) teaching materials in chapter 5 topic B. The method used is a quantitative approach with a pre-experimental one-group pretest-posttest design, involving 14 sixth-grade students. Observations, interviews, and essay tests were used to collect data. The results of the study showed that the data had a normal distribution, with a t-test value of 0.000 < 0.05 (Ha accepted), and an n-gain of 0.82 (indicating a high category), indicating that student learning outcomes had increased by 82.15%. Therefore, the guided inquiry model assisted by SIGAR teaching materials is effective in improving students' learning outcomes for IPAS because it can encourage active student participation and help develop critical thinking skills. Keywords: Guided inquiry, IPAS learning outcomes, SIGAR teaching materials